1997
DOI: 10.1093/clinchem/43.2.333
|View full text |Cite
|
Sign up to set email alerts
|

Medians for second-trimester maternal serum α-fetoprotein, human chorionic gonadotropin, and unconjugated estriol; differences between races or ethnic groups

Abstract: Second-trimester maternal serum α-fetoprotein (AFP), human chorionic gonadotropin (hCG), and unconjugated estriol (uE3) are routinely measured in screening fetuses at high risk for Down syndrome or open neural tube defects (ONTD). For test interpretation, individual patient values of these three analytes are related to population-derived median values. We evaluated data from >21 000 pregnancies to determine the extent of race-specific differences in median concentrations. For samples at most gestational… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
12
0
3

Year Published

2000
2000
2018
2018

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 55 publications
(15 citation statements)
references
References 9 publications
0
12
0
3
Order By: Relevance
“…It has been reported that serum levels of AFP, hCG, and uE3 were higher in Oriental than in Caucasian women [16–18]. In the present study, the medians of serum marker levels calculated at relevant GAs for the unaffected group were compared with published values for Caucasian women with unaffected pregnancies [12].…”
Section: Discussionmentioning
confidence: 88%
“…It has been reported that serum levels of AFP, hCG, and uE3 were higher in Oriental than in Caucasian women [16–18]. In the present study, the medians of serum marker levels calculated at relevant GAs for the unaffected group were compared with published values for Caucasian women with unaffected pregnancies [12].…”
Section: Discussionmentioning
confidence: 88%
“…The medians of AFP, free b-hCG and uE3 for each gestational weeks (from [14][15][16][17][18][19][20] were calculated, and regression modeling was performed to obtain the best fitted equation for predicted medians as a function of gestational age. Maternal weight adjustment was performed as previously described, 16,17 either log-linear or reciprocal-linear correction depending on the highest correlation coefficients.…”
Section: Discussionmentioning
confidence: 99%
“…The uE3 concentrations have been reported to be similar in samples of European and African descent, but have not been reported for Asians. 8 Benn et al 19 postulated that the marked differences observed in the various studies may probably be attributable to the inconsistent use of maternal weight correction, maternal age differences, heterogeneity in the gestational ages of the screened populations, and regional differences in the subpopulations of women included in each group. For the effective use of triple screens, all of these factors needed to be controlled.…”
Section: Discussionmentioning
confidence: 99%
“…There is a significant ethnic variation in serum levels of the placental‐derived analytes. Therefore, the development of multimarker screening requires an establishment of population‐specific MoM and regression algorithm . The racial‐associated variations may be from genetic, dietary or lifestyle differences .…”
Section: Alterations Of Serum Biomarkers Concentrations In Asian Ethnmentioning
confidence: 99%